Dicotomías técnicas para la "inevitabilidad" de la extracción de litio en América Latina - Folguera, Guillermo (2025)
Since 2015, the demand and price of lithium have increased considerably due to its central role in battery production. Latin America has around 60% of the world's lithium reserves. The deposits are mainly located in the Puna region shared by Chile, Bolivia, Peru and Argentina. The possibility of extracting lithium from salt flats is promoted by governments and companies as an undeniable opportunity. At the same time, lithium mining is presented as a key to solving the climate crisis, given the need to reduce greenhouse gases and favor the energy transition. In contrast, lithium extraction is considered by local communities as pernicious because the extraction involves the loss of large volumes of water, since lithium is dissolved in the salt flats and a large amount of fresh water is used during the process and because of the chemical contamination it generates. This paper will address the discursive and argumentative construction of lithium extraction. The general hypothesis is that lithium extraction is presented as inevitable as there are no other possible alternatives to the climate crisis, preventing its discussion in political terms.